Digital Scrapbook for Learning Recount Text in Junior High School - Audy Salsabillah; Ilza Mayuni (Stairs, 2021)
This study aimed to see the relevance of the contents of digital scrapbooks published by Kate Hadfield Designs with the Curriculum 2013 to learn recount text in Junior High School. The research data were the sentences which were stated in twenty digital scrapbooks from the Kate Hadfield Designs website katehadfielddesigns.com and Pinterest of Kate Hadfield Designs. The generic structure analysis proved that all the elements implemented in the text are well structured. The majority of the texts of digital scrapbooks have been written in the form of a language feature of recount text stated by experts. Nevertheless, the researcher still found several language features missing from some of the texts. For the social function, all the digital scrapbooks were in line with the Curriculum 2013. Furthermore, it could be concluded that the digital scrapbooks analyzed in this research accomplished the necessity of adequate recount text and was relevant with the Curriculum 2013.